STABLE CARBON AND OXYGEN ISOTOPIC COMPOSITIONS OF INDIAN CARBONATITES - Ray J.S.; Ramesh R. (My University, 2006)
Stable carbon and oxygen isotopic compositions of carbonatites are results of fractionation caused by various magmatic and post-magmatic processes during their generation and evolution. In the present work, we review available stable isotopic data from Indian carbonatites that span in age from Precambrian to Cretaceous. We explain the observed variations using various theoretical models and attempt to decipher the nature and temporal evolution of the mantle source(s) of these carbonatites. As observed elsewhere, δ18O variations are larger compared to those of δ13C. However, the average and mode of δ13C distributions in Indian carbonatites (~-4 ‰) are clearly higher than the global average. In general, δ13C and δ18O variations of Indian carbonatites can be grouped into (1) primary, unaltered carbonatites and (2) secondary, altered carbonatites. Primary variations are results of either batch crystallization under plutonic conditions, as observed in Hogenakal and northeastern Indian carbonatites, or fractional crystallization from CO2+H2O fluid-rich parent magmas, as observed in the rest. Secondary isotopic variations in all the carbonatites are apparently results of low temperature alteration by either meteoric water or CO2-bearing aqueous fluids. Estimated δ 18O values of the mantle sources of Indian carbonatites (5.3-7.5‰) show the expected normal mantle signatures, but δ13C values appear to be more variable (-6 to -3.1‰) than expected for a normal mantle. The younger carbonatites (<107 ma) in particular appear to have been derived from 13C enriched sources. Combined study of δ13C and 87Sr/86Sr data suggests that Indian carbonatites were derived from enriched mantle sources, and the enrichment probably took place some time in the Archean (~2.4 Ga). We suggest that the Indian sub-continental mantle, which was metasomatized by fluids from subducted oceanic crusts around that time, has remained a continuous source of carbonatites. Copyright © 2006 by V. H. Winston & Son, Inc. All rights reserved.
Keywords: Archean; Cretaceous; Cambrian; Precambrian::Archean; Докембрий::Архей; Mesozoic::Cretaceous; Мезозой::Меловая; Paleozoic::Cambrian; Палеозой::Кембрийская